Peran Literasi Keuangan dalam Memediasi Gaya Hidup Konsumtif dan Financial Self-Efficacy Terhadap Financial Well Being Mahasiswa di Kota Semarang - A’ida Fitriani; Diana Puspitasari; Amalia Nur Chasanah; Pradana Jati Kusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aimed to examine the relationship between a consumptive lifestyle and financial self-efficacy on the level of financial well-being of students in Semarang City, placing financial literacy as an intermediary variable. The approach used was quantitative with a survey design, involving 210 active students who were selectively determined through a purposive sampling technique. The data obtained were then analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS 3 application. The research findings indicate that financial self-efficacy plays an important role because it is proven to have a positive and significant influence on both financial well-being and financial literacy of students. On the other hand, a consumptive lifestyle also shows a positive and significant influence on financial well-being, but does not have a significant relationship with the level of financial literacy. Furthermore, financial literacy is not proven to have a significant effect on financial well-being and therefore is unable to mediate the relationship between a consumptive lifestyle and financial self-efficacy with financial well-being. From a theoretical perspective, these results confirm that psychological aspects reflected in an individual's self-confidence regarding financial management have a more dominant role than mere knowledge. Therefore, in practice, universities and related parties are advised to not only focus efforts on improving financial literacy, but also develop programs aimed at strengthening students' self-confidence in managing finances wisely and sustainably.